Pengaruh Pemberian Jus Wortel (Daucus Carota, Linn) Terhadap Kadar Glukosa Darah Mencit Putih Betina - Saputra, Hendra; Dharma, Surya; Suharti, Netty (Fakultas Farmasi Universitas Andalas, 2011)
A study of the effect of carrot juice (Daucus carota, Linn) on blood glucose levels in female white mice. This experiment used Advantage blood glucose meter (Roche) with enzymatic method. Length of treatment was for 21 days with a time of observation on day 7th, 14th and 21st. Carrot juice dose given was 0.52; 1.04 and 2.08 g/20 g BW. Results showed that the addition of carrot juice at all dose lower the blood glucose levels in mice significantly (P <0.05) after giving alloxan 3 mg/20 g body weight and glucose 195 mg/20 g BW.